P2Y12 antagonists and cardiac repair post-myocardial infarction: global and regional heart function analysis and molecular assessments in pigs. Issue 14 (14th August 2018) - Vilahur, Gemma; Gutiérrez, Manuel; Casani, Laura; Lambert, Carmen; Mendieta, Guiomar; Ben-Aicha, Soumaya; Capdevila, Antoni; Pons-Lladó, Guillem; Carreras, Francesc; Carlsson, Leif; Hidalgo, Alberto; Badimon, Lina
Abstract: Aims: P2Y12 antagonists are the standard in antiplatelet therapy but their potential effects on functional myocardial recovery and cardioprotection post-myocardial infarction (MI) are unknown. We investigated in a preclinical model of MI whether ticagrelor and clopidogrel differently affect cardiac repair post-MI. Methods and results: Pigs either received: (i) clopidogrel (600 mg; 75 mg/qd); (ii) ticagrelor (180 mg; 90 mg/bid); and (iii) placebo control. MI was induced by mid-left anterior descending coronary artery balloon occlusion (60 min) and animals received the maintenance doses for the following 42 days. Serial cardiac magnetic resonance was performed at Day 3 and Day 42 for the assessment of global and regional cardiac parameters. We determined cardiac AMP-activated protein kinase (AMPK), Akt/PKB, aquaporin-4, vascular density, and fibrosis. In comparison to controls, both P2Y12 antagonists limited infarct expansion at Day 3, although ticagrelor induced a further 5% reduction ( P  < 0.05 vs. clopidogrel) whereas oedema was only reduced by ticagrelor (≈23% P  < 0.05). Scar size decreased at Day 42 in ticagrelor-treated pigs vs. controls but not in clopidogrel-treated pigs. Left ventricular ejection fraction was higher 3 days post-MI in ticagrelor-treated pigs and persisted up to Day 42 ( P  < 0.05 vs. post-MI). Regional analysis revealed that control and clopidogrel-treated pigs had severe and extensive wall motion abnormalities in the jeopardized myocardium and a reduced myocardial viability that was not as evident in ticagrelor-treated pigs (χ 2 P  < 0.05 vs. ticagrelor). Only ticagrelor enhanced myocardial AMPK and Akt/PKB activation and reduced aquaporin-4 levels ( P  < 0.05 vs. control and clopidogrel). No differences were observed in vessel density and fibrosis markers among groups. Conclusions: Ticagrelor is more efficient than clopidogrel in attenuating myocardial structural and functional alterations post-MI and in improving cardiac healing. These benefits are associated with persistent AMPK and Akt/PKB activation.